Pemetaan Tata Kelola IT Menggunakan Standarisasi Cobit 4.1 (Studi Kasus UKMC Palembang) - Simbolon, Defrianti; Wijaya, Andri (LPPM UNIKA Santo Thomas Medan, 2019)
COBIT 4.1 is a standardization of framework mapping using a balanced scorecard that aims to implement information technology governance performance in UKMC. Information technology carried out in UKMC must be monitored and managed properly so as to avoid problems such as disrupted data security, data leakage, and organizational losses. Identification results obtained from COBIT 4.1 mapping obtained 21 sub domain processes that must be applied in UKMC such as PO (PO1, PO2, PO4, PO8, PO10), AI (AI, AI2, AI4, AI6, AI7), DS (DS1, DS2 , DS3, DS4 DS5, DS7, DS8, DS10, DS13), and ME (ME1, ME2). The sub domain of the process must be implemented and implemented in UKMC to support the achievement of the realization of good university governance and ensure that the information technology system that has been implemented in UKMC is aligned with the organization's goals so that the vision and mission of KSITK will run effectively and efficiently for UKMC development